2014
DOI: 10.3233/jad-131076
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of ERK/MAPK Overactivation in Prefrontal Cortex Reverses Early Memory Deficit in a Mouse Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) can be considered as a disease of memory in its initial clinical stages. Amyloid-β (Aβ) peptide accumulation is central to the disease initiation leading later to intracellular neurofibrillary tangles (NFTs) of cytoskeletal tau protein formation. It is under discussion whether different Aβ levels of aggregation, concentration, brain area, and/or time of exposure might be critical to the disease progression, as well as which intracellular pathways it activates. The aim of the present wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 66 publications
5
29
1
Order By: Relevance
“…These findings were consistent with those of previous studies of AD patients, that is, they have impairments of memory-guided reaching movement but not visually-guided reaching movement2728. From an age of 10 months, 3xTg mice exhibit pathological changes in the extraparietal areas of the cerebral cortex such as the frontal and temporal lobes4142. Further studies are required to elucidate whether these pathological changes are related to alterations in working memory in 3xTg mice that might affect their ability to accurately execute memory-guided limb movements during locomotion.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent with those of previous studies of AD patients, that is, they have impairments of memory-guided reaching movement but not visually-guided reaching movement2728. From an age of 10 months, 3xTg mice exhibit pathological changes in the extraparietal areas of the cerebral cortex such as the frontal and temporal lobes4142. Further studies are required to elucidate whether these pathological changes are related to alterations in working memory in 3xTg mice that might affect their ability to accurately execute memory-guided limb movements during locomotion.…”
Section: Discussionsupporting
confidence: 92%
“…MAZ was also identified as a blood biomarker in schizophrenia [39]. Accumulated evidence have shown that up-regulation of MAPK3 ( ERK1 ) are associated with the progression of Alzheimer's disease [40][44]. In addition, expression of MAPK3 is significantly associated with a locus (rs4583255[T]) on 16p11.2 which shows genome-wide significant association with psychosis, including schizophrenia, bipolar disorder and related psychoses by a recent GWAS (genome-wide association study) in a large cohort [45].…”
Section: Discussionmentioning
confidence: 99%
“…Upstream of cytokines production is the activation of the nuclear factor-kappa B (NF-κB) pathway,77 and the subsequent activation of mitogen-activated protein kinase (MAPK) pathways, whose proinflammatory gene expression is Aβ dependent 78. Extracellular signal-regulated protein kinases (ERKs), stress-activated protein kinases c-Jun NH2-terminal kinase (JNK), and p38 constitute the set of MAPKs whose action is exerted both in the cytoplasm and in the nucleus, thereby phosphorylating transcription factors.…”
Section: The Pathophysiology Of Neuroinflammation and Its Role In Alzmentioning
confidence: 99%